Low partograph completion in a public health facility in northern Uganda: a retrospective review of maternity records - Nassaka, Laillah; Udho, Samson (African Journal of Midwifery and Women's Health, 2022)
Low levels of partograph documentation and completion in Uganda by skilled health personnel is an ongoing problem. Completion of the partograph lowers the maternal mortality ratio by allowing for the early detection and management of childbirth complications, lowering the incidence of maternal death from preventable causes. However, there is a scarcity of recent studies focused on assessing partograph completion to the required standards. The aim of this study was to assess partograph documentation during monitoring of labour by skilled health personnel. A retrospective desk review of 400 partographs from women who laboured and gave birth at the Lira Regional Referral Hospital between 1 July and 31 December 2019 was conducted. A structured checklist was used to extract data on completion of the partograph. Only 5% of the partographs were filled to the required standards. Average documentation of the parameters of a partograph to the required standards was 45.1% for fetal monitoring, 44.8% for labour progress, and 15.6% for maternal monitoring. Documentation of different parameters of the partograph by skilled health personnel in public health facilities in northern Uganda was generally low. The Ministry of Health should strengthen partograph audit exercises and support supervision of and in-service capacity development training for skilled health personnel in high-volume facilities on partograph documentation.